1999
DOI: 10.1007/s007050050588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of mutations C-to-T1653 and T-to-C/A/G1753 of hepatitis B virus genotype C genome in chronic liver disease

Abstract: Among many mutational "hot spots" on hepatitis B virus (HBV) genome, A-to-T1762 and G-to-A1764 within the core promoter have been underscored in view of disease association as well as viral expression/replication. Although to a lesser extent, C-to-T1653 and T-to-V(C/A/G)1753 were also noteworthy in our previous study. To assess the clinical significance of these mutations, we determined the nucleotide sequence of an HBV DNA fragment covering these sites in HBsAg-positive blood donors (n = 160) and patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 20 publications
3
54
3
Order By: Relevance
“…Unfortunately, these methods are time consuming, labor intensive, and difficult to automate because they require a postamplification procedure, such as restriction enzyme digestion and electrophoresis. 21,22 The results of the present study indicate that real-time PCR with fluorescent hybridization probes represents a promising means of accurately identifying HBV mutants in patients with chronic HBV infections. Because the amount of PCR product amplified is monitored in each cycle and visualized, the technique provides rapid analyses of absolute template amounts without post-PCR steps.…”
Section: Discussionmentioning
confidence: 74%
“…Unfortunately, these methods are time consuming, labor intensive, and difficult to automate because they require a postamplification procedure, such as restriction enzyme digestion and electrophoresis. 21,22 The results of the present study indicate that real-time PCR with fluorescent hybridization probes represents a promising means of accurately identifying HBV mutants in patients with chronic HBV infections. Because the amount of PCR product amplified is monitored in each cycle and visualized, the technique provides rapid analyses of absolute template amounts without post-PCR steps.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, analysis of the nucleotide at position 1753 showed that a T-to-V (A/G/C) mutation increased to 46.8% in LC from 18.0% in CH, but dramatically decreased in HCC (22.9%) ( Table 4), suggesting that this mutation is associated with liver cirrhosis rather than HCC. In contrast, analysis of sera or plasma from Japanese subjects with AC, CH, LC and HCC infected with HBV genotype C showed that the percentage of T1753V mutation increased with progression of liver disease [41] . It is also reported that T1753V mutation was higher in HCC (53.2%) compared with LC (18.8%) and CH (9.8%) [31] .…”
Section: Discussionmentioning
confidence: 80%
“…In fact, T1753A/G/C mutations are usually present along with the existence of A1762T/ G1764A mutations. Previous data also demonstrated that T1753A/G/C mutations occurred later than the double BCP mutations in the natural course of chronic HBV infection (Takahashi et al, 1999). Regarding pre-S deletion, it has been shown in several reports that such mutant is an important risk factor of HCC (Chen et al, 2006;Choi et al, 2007).…”
Section: Discussionmentioning
confidence: 94%